Measuring adversity in the ABCD® Study: systematic review and recommendations for best practices - Florence J. Breslin; Erin L. Ratliff; Zsofia P. Cohen; Julie M. Croff; Kara L. Kerr (BMC Medical Research Methodology)
Abstract Background Early life adversity (ELA) has substantial, lifelong impacts on mental and physical health and development. Data from the ABCD® Study will provide essential insights into these effects. Because the study lacks a unified adversity assessment, our objective was to use a critical, human-driven approach to identify variables that fit ELA domains measured in this study. Methods We clarify best practices in measurement of adversity in the ABCD Study through the creation of adversity scores based on the well-established Adverse Childhood Experiences (ACEs) questionnaire and another inclusive of broader ELA. Variables previously used to measure adversity in the ABCD dataset were determined via literature review. We assessed each variable to identify its utility in measuring domains of adversity at baseline and follow-up time points and by individual completing the assessment (i.e., youth or caregiver). Variables were selected that align with decades of ELA measurement, and therefore, can be used by research teams as measures of ELA. Results The literature review and critical analysis of items led to the development of three measures of ELA: an ACES-proxy score, a youth-reported ACEs-proxy score, and a broader ELA score (ELA+). We provide code using R to calculate these scores and their constituent domains for use in future ABCD adversity-related research. Conclusions The ABCD Study is one of the largest longitudinal studies of youth development, with data available for secondary analysis. Our review of existing measures and development of a coding schema will allow examination of ELA using this dataset, informing our understanding of risk, resilience, and prevention.